The impact of treatment condition and the lagged effects of PTSD symptom severity and alcohol use on changes in alcohol craving. (April 2016) - Kaczkurkin, Antonia N.; Asnaani, Anu; Alpert, Elizabeth; Foa, Edna B.
Abstract: Given the high rates of comorbidity between posttraumatic stress disorder (PTSD) and substance use disorder (SUD), we investigated an integrated treatment for these disorders. Individuals with comorbid PTSD and alcohol dependence were randomized to receive naltrexone or placebo, with or without prolonged exposure (PE). All participants also received BRENDA (supportive counseling). The naltrexone plus PE group showed a greater decline in alcohol craving symptoms than those in the placebo with no PE group. The PE plus placebo and the naltrexone without PE groups did not differ significantly from the placebo with no PE group in terms of alcohol craving. No treatment group differences were found for percentage of drinking days. Alcohol craving was moderated by PTSD severity, with those with higher PTSD symptoms showing faster decreases in alcohol craving. Both PTSD and alcohol use had a lagged effect on alcohol craving, with changes in PTSD symptoms and percentage of days drinking being associated with subsequent changes in craving. These results support the relationship between greater PTSD symptoms leading to greater alcohol craving and suggest that reducing PTSD symptoms may be beneficial to reducing craving in those with co-occurring PTSD/SUD. Highlights: Secondary analysis of alcohol/PTSD treatment included naltrexone or placebo, with or without PE. All participants also received BRENDA (supportive counseling). Naltrexone + PE showed a faster decline in alcohol craving compared to Placebo + NoPE. PTSD moderated alcohol craving and both PTSD and alcohol use had a lagged effect on alcohol craving. These results suggest that reducing PTSD symptoms may be beneficial to reducing alcohol craving.